Marketing Channel Analysis in an Effort to Develop the Potential of Bananas in Pinrang Regency - Raissa Dina Paridy; Masitah Masitah; Doddy Ismunandar Bahari (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
Banana is one of the agriculture that has bright prospects in both the domestic and export markets, but banana farmers do not understand the potential of this banana. Therefore, a system is needed so that farmers know about the banana prospects. In marketing, until now there are still some discussions about the marketing patterns used are still quite long from farmers to consumers, increasing marketing costs incurred, marketing large margins, the benefits of each marketing institution and marketing of banana assistance. It dramatically affects the marketing of bananas in Pinrang Regency. The purpose of this study was to analyze the marketing patterns of Kepok bananas in Pinrang Regency. Determination of the sample in a study involving banana farmers, collector traders, wholesalers and retailers using the snow-balling method, samples related to all that was questioned, with the sample calculation were 30 banana farmers and 7 traders. The analytical method uses descriptive qualitative (quantitative) and quantitative (margin calculation) analysis. The results of this study indicate that farmers market their banana through two marketing channels in Pinrang Regency. There are two marketing channels, 1st channel is Farmer to Consumer, 2nd channel is Farmer to Collector Trader then to Retailer Trader and ends in Consumer. The involved marketing institutions require costs to operate marketing functions such as loading costs, transportation costs, fees, consumption and so forth.